MACROBENTHIC COMMUNITY STRUCTURE DURING FALLOW SEASON IN KOLE PADDY FIELDS, NORTHERN KERALA, INDIA - S., Vineetha (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2016)
Despite the recognized contribution of benthic fauna in nutrient enhancement, very little information isavailable from Indian paddy fields. This study analyzed the benthic community structure during fallow seasonin Kole paddy fields, a part of Vembanad Kole wetlands (a Ramsar site), Northern Kerala, India. Study area during fallow season was characterized by isolated water patches amidst of terrestrial vegetation (grass). Themacrobenthic fauna belonged to the phyla Annelida, Arthropoda, Mollusca and families Tubificidae, Naididae,Chironomidae, Ceratopogonida, Chaoboridae, Ceratopogonidae, Gyrinidae and Bithynidae. These organisms possessed various survival mechanisms that ensured their survival against dry periods. Insects were the majorbenthic organisms; the habitat fragmentation due to isolated distant water patches during fallow season favoredinsect taxa more due to their active/flight mode of dispersal compared to oligochaetes which are benthiccrawlers. Macrobenthic abundance was less (166±60 ind./m2), attributed to reduced habitable area for benthosdue to habitat desiccation. A decline in abundance was apparent from January to June 2010, the beginning toend of fallow season except in April where the onset of rain after a dry spell made the dry area wet, therebymaking the inactive dormant forms of organisms live, resulting in an increased abundance. Diversity analysis of benthic families revealed that highest richness (d) of 1.235 was in March and diversity (H') of 2.603 was inMarch. No significant correlation emerged between benthic abundance and the measured environmentalparameters, implying that the interaction of biota and physico chemical variables was overridden by some other unmeasured factors.